Foresight Strategy in Identifying Drivers of Change for the Development of Aloeland Edu-tourism Based on Circular Economy - Azhar Maulana; Epsi Euriga; Mastur Mastur (PAKIS JOURNAL INSTITUTE, 2026)
Aloeland edutourism at P4S Mountvera Sejati holds significant potential as an aloe vera agribusiness and training center, yet the application of circular economy principles remains suboptimal. This study aims to identify the drivers of change influencing Aloeland’s development within a circular economy framework, providing a foundation for future scenarios and adaptive strategies. The research employed a qualitative descriptive approach with zero waste principles, using in-depth interviews, focus group discussions, participatory observation, and literature review. Data were analyzed through the PESTLE framework (political, economic, socio-cultural, technological, legal, environmental) to capture relevant external factors. Findings reveal that political drivers include government policies on community-based tourism and zero waste programs; economic drivers emphasize business diversification and value-added aloe vera by-products; social drivers are supported by community participation and youth involvement; technological drivers involve AI, IoT, and waste-processing innovations legal drivers highlight cooperative legality and herbal product standardization; environmental drivers stress adaptation to climate crises and resource conservation. The study concludes that integrating foresight with circular economy enables the formulation of adaptive strategies that enhance competitiveness, business efficiency, and Aloeland’s role as a sustainable agro-edutourism destination.